Phylogenetic Analysis Related to Hepatitis B Virus based on Region Surfaces in Tuban, East Java Province, Indonesia - Supiana Dian Nurtjahyani; Retno Handajani (Indian Journal of Forensic Medicine & Toxicology, 2021)
Hepatitis B virus (HBV) is a virus cause liver disease. This virus could be transmitted through blood product,and it becomes the major problems in developing countries. Genotype distribution of HBV depends ongeographical characteristics. Here, we reported HBV genotyping analysis of blood donors with positiveHepatitis Surface Antigen (HbsAg) at Indonesian Red Cross Foundation in Tuban, East Java. Total 150sera were collected from blood donors at Indonesian Red Cross Foundation in Tuban, East Java. Enzyme-Linked Immunosorbent Assay (ELISA) was conducted by PRISM®HBsAg kit (ABBOTT) according tothe manufacture’s instruction, to determine sample that has positive HbsAg. The genotyping analysis wasdone using polymerase chain reaction and sequencing method from 12 samples. Genetyx ver.10 softwarewas used for identification of HBV type. Analysis of HBV genotype revealed three different types of HBV.HBV type B was the major HBV (50%). Interestingly, there was one unidentified HBV type suggested as anovel subtype of HBV. Further genotyping analysis is needed to confirm novelty of the unidentified HBVtype. Analysis of HBV genotype revealed three different types of HBV. HBV type B was the major HBV(50%). Interestingly, there was one unidentified HBV type suggested as a novel subtype of HBV. Furthergenotyping analysis is needed to confirm novelty of the unidentified HBV type. This study was the firstevidence of blood donor’s genotyping analysis in Tuban.